THE PREVALENCE OF ATROPHIC GASTRITIS IN DYSPEPTIC PATIENTS AND ITS RISK FACTORS: Pharmaceutical Sciences- Medicine - SALEH, AZADBAKHT; MOSAYEB, MORADNIANI; SABZEVARI ZOHRE, MIRBEIK-; SALEHEH, AZADBAKHT; ASGHAR, AALIEHPOUR (International Journal of Life Science and Pharma Research, 2018)
Gastric cancer is the fourth most common cancer after lung, breast and colorectal cancer. The development of gastric cancer (GC) includes gastritis, atrophic gastritis (AG), intestinal metaplasia, dysplasia and gastric cancer as well. Atrophic gastritis (AG) has been identified as a risk factor for GC and cancer incidence is associated with the severity and extension of AG. This study aimed to evaluate the prevalence of AG and its risk factors in dyspeptic patients. This is a cross-sectional study. A total of 1650 dyspeptic patients presented to endoscopy department in Shohada-y-Ashayer and Shahid Rahimi hospitals in Khorramabad, Iran were selected and invited to participate in the study during October 2015 to August 2016. In patients with gastric lesion, the biopsy sample was taken from lesion. Data were analyzed by SPSS.ver.22. 1016 patients were studied. The mean age of the patients was 47±16 years. According to pathologic findings, the prevalence of AG was 12.2% (124/1016); with the prevalence of mild, moderate and severe AG of 54.8% (68/124), 32.3% (40/124) and 12.9% (16/124) respectively. Statistical analysis showed significant association between AG with age (p˂0.001), BMI (p=0.007), place of residence (p˂0.001), education (p=0.001) and smoking (p=0.021). The results showed that the prevalence of AG in dyspeptic patients is in a high range. AG is a risk factor for gastric cancer. Based on the relationship between age, BMI, place of residence, educational level and smoking with AG, it is recommended to provide prevention procedures of gastric cancer in elderly dyspeptic patients.